(untitled) (Revista Apotheke, 2017)
The purpose of this project is to analyze the main changes that occurred inBrazilian painting from the chromatic point of view. It is intended to show how gradually Brazilian painting acquires certain stylistic autonomy precisely insofar as painters emphasize the expressive properties of color and space.